Amygdala and hippocampus fail to habituate to faces in individuals with an inhibited temperament - Blackford, Jennifer Urbano (Oxford University Press, 2013)
Habituation is a basic form of learning that reflects the adaptive reduction in responses to a stimulus that is neither threatening nor rewarding. Extremely shy, or inhibited individuals, are typically slow to acclimate to new people, a behavioral pattern that may reflect slower habituation to novelty. To test this hypothesis, we used functional magnetic resonance imaging to examine habituation to neutral faces in 39 young adults with either an extreme inhibited or extreme uninhibited temperament. Our investigation focused on two key brain regions involved in response to novelty—the amygdala and the hippocampus. Habituation to neutral faces in the amygdala and hippocampus differed significantly by temperament group. Individuals with an uninhibited temperament demonstrated habituation in both the amygdala and hippocampus, as expected. In contrast, in individuals with an inhibited temperament, the amygdala and hippocampus failed to habituate across repeated presentations of faces. The failure of the amygdala and hippocampus to habituate to faces represents a novel neural substrate mediating the behavioral differences seen in individuals with an inhibited temperament. We propose that this failure to habituate reflects a social learning deficit in individuals with an inhibited temperament and provides a possible mechanism for increased risk for social anxiety.